Musāhamātu Fa’āliyati li al-Duktūri Syauqi Ḍaifi fī Taisīri al Nahwi - Thalib, Ismail Mohamed (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2021)
This study has reviewed Dr. Shawqi Daif’s idea on the renewal of Arabic language grammar between theory and practice. In order to enhance the Arabic language that could be used like other popular languages, its grammar needs to be simplified from its traditional and complicated attributes. The aim of the research is to focus on simplified grammar method introduced by Dr. Shawki Daif and to highlight the significant contribution of his work in the field of Arabic language. The simplified method helps the new Arabic language learners to quickly grasp the language. In order to analyze the idea of Dr. Shawki Daif, information has been collected from various sources. This paper has been written with the objective exploring the contribution of Dr.Shawki Daif and presenting his value added work for wider popularity among Arabic learners especially the non Arabic speakers. This research concludes that the simplified grammar method is more useful to Arabic learners and the usage of Arabic language will be increased in various fields of studies